Phosphoinositide-3-Kinase Is the Primary Mediator of Phosphoinositide-Dependent Inhibition in Mammalian Olfactory Receptor Neurons - Ukhanov, Kirill; Corey, Elizabeth; Ache, Barry W. (Frontiers in Cellular Neuroscience, 2016)
Odorants inhibit as well as excite primary olfactory receptor neurons (ORNs) in many animal species. Growing evidence suggests that inhibition of mammalian ORNs is mediated by phosphoinositide (PI) signaling through activation of phosphoinositide 3-kinase (PI3K), and that canonical adenylyl cyclase III signaling and PI3K signaling interact to provide the basis for ligand-induced selective signaling. As PI3K is known to act in concert with phospholipase C (PLC) in some cellular systems, the question arises as to whether they work together to mediate inhibitory transduction in mammalian ORNs. The present study is designed to test this hypothesis. While we establish that multiple PLC isoforms are expressed in the transduction zone of rat ORNs, that odorants can activate PLC in ORNs in situ, and that pharmacological blockade of PLC enhances the excitatory response to an odorant mixture in some ORNs in conjunction with PI3K blockade, we find that by itself PLC does not account for an inhibitory response. We conclude that PLC does not make a measurable independent contribution to odor-evoked inhibition, and that PI3K is the primary mediator of PI-dependent inhibition in mammalian ORNs.